The Impact of Cybercrime on Security in Africa: A Case Study of Côte d'Ivoire - Belhaouari, Zohra; Fasla, Abdellatif (Journal of Legal Studies and Researches, 2026)
Cybercrime constitutes one of the most pressing legal and security threats undermining the foundations of legal certainty and institutional stability in African states, particularly in light of fragile digital infrastructure, insufficient legislative frameworks, and limited effectiveness of judicial and law enforcement institutions. This study seeks to analyze the legal and security ramifications of cybercrime through an applied case study of the Republic of Côte d’Ivoire, a country experiencing significant digital expansion coupled with a notable rise in cyber-related criminal activities. The analysis reveals that several factors have contributed to the exacerbation of this phenomenon, including the rapid increase in internet accessibility, high youth unemployment rates, and low levels of awareness of digital legal culture. The primary offenses observed include cyber fraud, identity theft, and extortion via digital platforms, all of which pose a serious threat to public digital order and compromise national cybersecurity A major challenge identified is the inadequacy of domestic legislation in keeping pace with the evolving nature of cybercriminal methods, compounded by the shortage of specialized technical competencies within law enforcement bodies, thereby weakening the effectiveness of criminal investigation and prosecution mechanisms.